Results of a Beer Game Experiment: Should a Manager Always Behave According to the Book? - Edali, Mert; Yasarcan, Hakan (WILEY-HINDAWI, 2016)
We investigate the effect of the literature suggested optimal values of the parameters of a dynamic decision-making heuristic in the presence of semirationally managed supply chain echelons using a soft coded one-to-one version of The Beer Game as an experimental platform. According to the counterintuitive results obtained in this study, it is possible for a rational manager to obtain higher costs than the costs generated by a semirational manager. Thus, the results do not support the use of the well-established decision parameter values for the echelon of concern if the other echelons' inventories are managed suboptimally. (C) 2015 Wiley Periodicals, Inc.
Keywords: anchor-and-adjust heuristic; artificial agents; beer game; stock management; supply chain management; DECISION-MAKING; DETERMINISTIC CHAOS; SUPPLY CHAINS; STATE; Mathematics; Science & Technology - Other Topics